Organizational Supports for Research Evidence Use in State Public Health Agencies: A Latent Class Analysis. Issue 4 (July 2019) - Hu, Hengrui; Allen, Peg; Yan, Yan; Reis, Rodrigo S.; Jacob, Rebekah R.; Brownson, Ross C.
Abstract : Objective: Use of research evidence in public health decision making can be affected by organizational supports. Study objectives are to identify patterns of organizational supports and explore associations with research evidence use for job tasks among public health practitioners. Design: In this longitudinal study, we used latent class analysis to identify organizational support patterns, followed by mixed logistic regression analysis to quantify associations with research evidence use. Setting: The setting included 12 state public health department chronic disease prevention units and their external partnering organizations involved in chronic disease prevention. Participants: Chronic disease prevention staff from 12 US state public health departments and partnering organizations completed self-report surveys at 2 time points, in 2014 and 2016 (N = 872). Main Outcome Measures: Latent class analysis was employed to identify subgroups of survey participants with distinct patterns of perceived organizational supports. Two classify-analyze approaches (maximum probability assignment and multiple pseudo-class draws) were used in 2017 to investigate the association between latent class membership and research evidence use. Results: The optimal model identified 4 latent classes, labeled as "unsupportive workplace, " "low agency leadership support, " "high agency leadership support, " and "supportive workplace." With maximum probability assignment, participants in "high agency leadership support" (odds ratio = 2.08; 95% CI, 1.35-3.23) and "supportive workplace" (odds ratio = 1.74; 95% CI, 1.10-2.74) were more likely to use research evidence in job tasks than "unsupportive workplace." The multiple pseudo-class draws produced comparable results with odds ratio = 2.09 (95% CI, 1.31-3.30) for "high agency leadership support" and odds ratio = 1.74 (95% CI, 1.07-2.82) for "supportive workplace." Conclusions: Findings suggest that leadership support may be a crucial element of organizational supports to encourage research evidence use. Organizational supports such as supervisory expectations, access to evidence, and participatory decision making may need leadership support as well to improve research evidence use in public health job tasks. Abstract : Supplemental Digital Content is Available in the Text.